“Bitter” manioc (Manihot esculenta): its consumption and the grater used by the indigenous peoples of the Gran Chaco in its preparation - Nicolás M. Kamienkowski; Pastor Arenas (Journal de la Société des Américanistes)
This paper discusses the cultivation of “bitter” manioc (Manihot esculenta) by the ethnic groups of the Gran Chaco, the preparing for consumption, and also the grater used in the process. It includes a bibliographical review on the subject, and the results of a study made of the graters in different ethnographic museums around the world. Field investigations provided clear evidence of cultivation of the plant, the way in which it was prepared and consumed, as well as the characteristics of the grater. They confirmed consumption of “bitter” manioc by the Maká, Nivaclé, Lengua-Maskoy and Choroti-Manjuy peoples, the steps in preparing it and the peculiarities of the grater used. This plant, the way in which it was cooked and the use of the grater are now practically lost among the ethnic groups of the Gran Chaco.